AN ERROR ANALYSIS OF PREPOSITION USAGE IN WRITING PROCEDURE TEXT BY STUDENTS AT SMA HKBP SIDORAME - Rina Octavia Simarmata; Salom Tampubolon; Susi Era Lumbangaol; Maria Olivia Christina Sianipar (Merwin Publisher, 2023)
Writing is one of the important skills in studying English. Writing is an activity that is productive and expressive. The objectives of this research to identify the types of errors and most common errors made by the students’ in writing procedural text at SMA HKBP Sidorame. The research designed this study with mix qualitative and quantitative method with the data from students’ writing test. The findings show that: the dominant error were made by the tenth grade students of SMA Negeri 1 Barru was selection. The total incorrect error was 121. It consisted of three kinds of error, namely committed 54 errors or 47%, Then, error in omission consists of 38 errors or 31%, and the last insertion consisted of 26 errors or 22%.